(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
In their book "Women of the Wall, Navigating Religion in Sacred Sites", Y. Johan and N. Perez aim to present and analyse the feminist movement of "Nashot HaKotel" highliting their key role in struggle for religious equality in Israel and the Jewish World.